1992
DOI: 10.1034/j.1399-3054.1992.850410.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three DNA fluorochromes for flow cytometric estimation of nuclear DNA content in plants

Abstract: S. 1992. Comparison of three DNA fluorochromes for flow cytometric estimation of nuclear DNA content in plants. -Physiol. Plant. 85:'625-631.Flow cytometric estimation of nuclear DNA content was performed in sis plant species employing three fluorochromes showing different DNA base preferences: propidium iodide (no base preference), 4',6-diamidino-2-phenylindole (DAPI; AT preference), and mithramycin (GC preference). Nuclei isolated from human leukocytes were used as a primary reference standard. While nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(164 citation statements)
references
References 15 publications
4
148
0
2
Order By: Relevance
“…In addition to the target species, Solanum lycopersicum L. (2C = 1.96 pg and AT = 64.5%; Doležel et al 1992;Meister and Barow 2007) was also cultivated and used as primary internal standard. Seeds were generously supplied by Jaroslav Doležel (Experimental Institute of Botany, Olomouc, Czech Republic).…”
Section: Plant Materialsmentioning
confidence: 99%
“…In addition to the target species, Solanum lycopersicum L. (2C = 1.96 pg and AT = 64.5%; Doležel et al 1992;Meister and Barow 2007) was also cultivated and used as primary internal standard. Seeds were generously supplied by Jaroslav Doležel (Experimental Institute of Botany, Olomouc, Czech Republic).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Ploidy level was estimated according to Brito et al (2008) using Pisum sativum cv. Ctirad as the internal standard (2C = 9.09 pg; Doležel et al 1992). Briefly, nuclei were released by chopping with a razor blade half of a leaf of the olive plant and of P. sativum, in LB01 buffer (Doležel et al 1989).…”
Section: Flow Cytometric Analysesmentioning
confidence: 99%
“…7.6.1.1 Choice of Fluorochromes Following the publication of Galbraith et al's paper (1983), a diverse range of fluorochromes was employed for genome size estimation, which is broadly divided into two groups: (i) the DNA intercalating dyes, including propidium iodide and ethidium bromide, and (ii) base-specific fluorochromes, including mithramycin, chromomycin, olivomycin, DAPI and Hoechst. However, in a series of studies Doležel and colleagues (Doležel et al 1992(Doležel et al , 1998 showed that only intercalating dyes were suitable for the accurate estimation of genome size. Further, in a largescale comparative study involving four laboratories, Doležel et al (1998) demonstrated that there was excellent agreement between results obtained using either Feulgen microdensitometry or FCM if propidium iodide was used as the fluorochrome.…”
Section: The Development Of Flow Cytometry For Genome Size Estimationmentioning
confidence: 99%